Lanthanide phosphonates with pseudo-D-5h local symmetry exhibiting magnetic and luminescence bifunctional properties - Ren, Min
Two lanthanide(III) phosphonates [Ln(notpH(4))(H2O)]ClO4 center dot 3H(2)O [Ln = Dy(1), Ho(2)] in which the lanthanide ion has a pseudo-D-5h symmetry have been reported. Both show layer structures where the neighbouring lanthanide atoms are connected by a pair of O-P-O bridges. Magnetic studies reveal that field-induced slow relaxation can be observed in both cases. Complex 1 is of particular interest because it shows not only field-tunable dual relaxation processes originating from the single ion anisotropy as well as the spin collective effect, but also simultaneous emissions from the metal ion, the ligand and the radiative energy transfer from the ligand to metal. The emission of Dy-III can be correlated to the magnetic data.